The taboo of cancer: the experiences of cancer disclosure by Iranian patients, their family members and physicians. Issue 2 (2nd December 2011) - Zamanzadeh, Vahid; Rahmani, Azad; Valizadeh, Leila; Ferguson, Caleb; Hassankhani, Hadi; Nikanfar, Ali‐Reza; Howard, Fuchsia
Abstract Objective The objective of this study is to describe the experiences of cancer disclosure by Iranian cancer patients, their family members and physicians. Methods Twenty cancer patients, ten family members and eight physicians participated in this study. Data were collected via semi‐structured, in‐depth interviews and analyzed using qualitative content analysis. Results Three categories were identified: cancer avoidance, a climate of non‐disclosure and mutual concern. The findings demonstrated that cancer is a taboo subject and the word cancer, as well as other indicative terms, was rarely used in daily communication. A climate of non‐disclosure predominated because patients were the last to know their diagnosis, they were unaware of their prognosis, and family members and physicians employed strategies to conceal this information. The mutual concern of patients, family members and physicians was the main reason that cancer was not discussed. Conclusion Cancer is a taboo subject in Iran that is maintained and reinforced primarily because of the mutual concern of patients, family members and physicians. The first step to address this taboo and inform cancer patients of their diagnosis would be to understand and help mitigate the individual, family and social consequences of disclosure. Copyright © 2011 John Wiley & Sons, Ltd.